High-hardness scratch-resistant artistic coating as well as preparation method and application thereof
By combining modified epoxy acrylic emulsion with silicon nitride and bamboo powder, the problem of artistic paint falling off and peeling in low temperature environments is solved, and the high hardness and scratch resistance are improved, satisfying the durability of high-end decoration Sexual needs.
Patent Information
- Application Number
- CN202411559654.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2024-12-27
AI Technical Summary
Existing artistic paints are prone to peeling and peeling problems in low temperature environments, resulting in a decrease in scratch resistance and making it difficult to meet the needs of high hardness and durability.
Modified epoxy acrylic emulsion is used as the film forming substance, through the condensation reaction of vinyl triethoxysilane with glass fiber, combined with epoxy resin and acrylic resin, silicon nitride and bamboo powder are added as wear-resistant fillers to form a dense Organic polymer-inorganic filler three-dimensional spatial structure to improve the mechanical properties of the coating.
Maintain good toughness and scratch resistance in low temperature environments, extend service life, improve the wear resistance and durability of the coating, and reduce costs.
Smart Images

Figure QW89VPZ4RQFCTDXG59G9JJEE1BC8JRNLXIUHYU5J
Abstract
Description
Technical Field
[0001] The present application relates to the field of coatings, and more particularly, to a high-hardness, scratch-resistant artistic coating and a preparation method and application thereof. Background Art
[0002] Artistic paint is a new type of wall decoration material that combines the advantages of traditional paint and artistic elements, providing a more colorful choice for wall decoration. With its unique color, texture and texture, artistic paint gives the wall a high decorative effect and personalized style.
[0003] In existing technologies, the main formulation of artistic coatings includes resin, fillers, pigments, water, and additives such as dispersants, leveling agents, and preservatives. The formulation of coatings varies significantly depending on the application scenario and product positioning. In the high-end decoration market, artistic coatings need to possess high hardness and scratch resistance to withstand daily wear and tear, achieving long-term durability.
[0004] To achieve high hardness and scratch resistance, coatings typically incorporate large amounts of fillers with properties such as high hardness, high strength, and wear resistance, such as silicon nitride and aluminum oxide. However, the large addition of wear-resistant fillers can increase the brittleness of the coating, making it prone to shedding and peeling, especially in low-temperature environments. Summary of the Invention
[0005] In order to ensure that the coating still has good scratch resistance in a low temperature environment, the present application provides a high-hardness scratch-resistant artistic coating and its preparation method and application.
[0006] In a first aspect, the present application provides a high-hardness, scratch-resistant artistic coating, which adopts the following technical solution: A high-hardness, scratch-resistant artistic coating comprising the following components in parts by weight: 30-40 parts of modified epoxy acrylic emulsion; 8-15 parts of wear-resistant filler; 15-20 parts of titanium dioxide; Dispersant 0.4-0.8 parts; 0.2-0.5 parts of leveling agent; Defoaming agent 0.1-0.3 parts; 0.1-0.2 parts of preservatives; 25-35 parts water; The preparation process of the modified epoxy acrylic emulsion is as follows: The first step is to mix 3-5 parts of vinyltriethoxysilane and 20-30 parts of 70-80 wt% ethanol solution, heating to 35-40° C., and stirring for 20-30 minutes to obtain a modified solution; The second step is to mix 10-15 parts of glass fiber and 60-80 parts of water, ultrasonically disperse for 30-60 minutes, then add the above-mentioned modification liquid, heat to 60-70°C, continue stirring for 2-3 hours, then filter, wash with water, and dry to obtain modified glass fiber; The third step is to add all the modified glass fibers into 80-100 parts of water, ultrasonically disperse for 30-60 minutes, then add 0.3-0.5 parts of sodium dodecylbenzene sulfonate, raise the temperature to 55-60°C, then add a mixture of 6-8 parts of epoxy resin, 20-25 parts of methyl methacrylate, 30-40 parts of butyl acrylate and 2-3 parts of methacrylic acid, then raise the temperature to 70-75°C, add 2-3 parts of 10wt% ammonium persulfate solution, stir evenly, and react for 1-2 hours to obtain a modified epoxy acrylic emulsion.
[0007] By adopting the above-mentioned technical solution, the artistic coating of this application optimizes and modifies the film-forming material. Vinyltriethoxysilane, a silane coupling agent, contains a vinyl functional group and three hydrolyzable ethoxy groups in its molecular structure. During the preparation process, it hydrolyzes into silanol groups, which undergo a condensation reaction with the hydroxyl groups on the surface of the glass fiber, forming a chemical bond and achieving graft modification on the glass fiber surface. The modified glass fiber participates in the polymerization reaction of the epoxy acrylic emulsion. Under the action of an initiator, the unsaturated double bond undergoes an addition reaction with the resin, resulting in the grafting of the modified glass fiber onto the molecular chain of the epoxy acrylic polymer, completing the modification.
[0008] As a man-made inorganic fiber, glass fiber has the characteristics of high strength, light weight, good dimensional stability, and high hardness. The coating film formed by the modified epoxy acrylic emulsion has excellent mechanical properties, especially in low temperature environments, showing good toughness and not prone to falling off or peeling.
[0009] Epoxy acrylic emulsions combine the advantages of epoxy and acrylic resins, retaining the high strength and modulus of epoxy resins, resulting in excellent mechanical properties. The addition of acrylic resin improves the epoxy resin's weather resistance, extending its service life. Furthermore, compared to acrylic and epoxy resin emulsions, epoxy acrylic emulsions offer better compatibility with wear-resistant fillers. The film-forming substance uses water as a solvent, making it environmentally friendly, easy to apply, and convenient to store.
[0010] The addition of wear-resistant fillers further enhances the coating's mechanical properties, resulting in high hardness, excellent wear resistance, and scratch resistance. The addition of titanium dioxide improves hiding power and ensures the coating's decorative effect. Dispersants, leveling agents, defoamers, and preservatives serve as additives to facilitate coating preparation and application, ensuring coating quality.
[0011] Optionally, the wear-resistant filler comprises silicon nitride and bamboo powder in a mass ratio of (2-3):1.
[0012] By adopting this technical solution, silicon nitride, a ceramic material with excellent properties and very high hardness, can be added to the coating to form a dense three-dimensional structure of organic polymer and inorganic filler, improving the coating's wear, scratch, and abrasion resistance, while also enhancing its durability. The addition of bamboo powder can replace a portion of the silicon nitride, reducing costs while maintaining the same excellent mechanical properties. It also helps improve the coating's adhesion to the wall and enhance its low-temperature performance.
[0013] Optionally, 2-3 parts of a compatibilizer are further included by weight; the preparation process of the compatibilizer is as follows: first, peel, core and chop avocados, then heat them with steam to 100-110° C. for 3-5 minutes, then use a screw oil press to press the steamed avocados, the pressing temperature is controlled at 60-80° C. and the pressure is 10-20 MPa, and the compatibilizer is obtained after filtering.
[0014] Optionally, the added amount of the wear-resistant filler is 13-15 parts.
[0015] By adopting the above technical solution, avocado oil is used as a compatibilizer, which is rich in monounsaturated fatty acids and helps to improve the compatibility of wear-resistant fillers with polymer emulsions, so that the addition amount of wear-resistant fillers can be higher, thereby improving the mechanical properties of the coating such as scratch resistance.
[0016] Optionally, the particle size of the silicon nitride is 5-10 μm, and the particle size of the bamboo powder is 0.3-0.5 μm.
[0017] By adopting the above technical solution, the particle size of silicon nitride is larger than that of bamboo powder, forming a compound, so that the coating has both scratch resistance and low temperature performance.
[0018] Optionally, the dispersant is a polycarboxylate ammonium salt dispersant.
[0019] By adopting the above technical solution, the polycarboxylate ammonium salt dispersant is a water-soluble polymer compound that can form a colloidal solution in water, has adsorption and cross-linking capabilities, can interact with ions in water, and helps to improve the stability of the dispersion system.
[0020] Optionally, the leveling agent is a silicone leveling agent.
[0021] By adopting the above technical solution, the silicone leveling agent has a lower surface tension, which helps to improve the fluidity of the coating and the flatness of the coating film, and can eliminate surface defects caused by poor surface tension, such as shrinkage holes, ripples, blooming and orange peel phenomena.
[0022] Optionally, the defoaming agent is a mineral oil defoaming agent.
[0023] By adopting the above technical solution, the mineral oil defoamer can be used in various water-based systems, has stable chemical properties, is safe and reliable, is non-toxic and harmless, does not produce adverse side effects, can quickly eliminate foam, and has a long foam suppression effect.
[0024] In a second aspect, the present application provides a method for preparing a high-hardness, scratch-resistant artistic coating, using the following technical solution: A method for preparing a high-hardness, scratch-resistant artistic coating comprises the following steps: mixing a modified epoxy acrylic emulsion, a wear-resistant filler, titanium dioxide, a dispersant, a leveling agent, a defoaming agent, a preservative and water according to the required weight parts of the formula to obtain the high-hardness, scratch-resistant artistic coating.
[0025] By adopting the above technical solution, the preparation method is simple.
[0026] In a third aspect, the present application provides an application of a high-hardness, scratch-resistant artistic coating in wall decoration.
[0027] In summary, this application has the following beneficial effects: 1. This application uses glass fiber to modify epoxy acrylic acid as a film-forming material. Glass fiber, as an artificial inorganic fiber, has the characteristics of high strength, light weight, good dimensional stability, high hardness, etc., so that the coating film formed by the modified epoxy acrylic acid emulsion has excellent mechanical properties, especially in low temperature environments, it shows good toughness and is not easy to fall off or peel.
[0028] 2. This application utilizes a combination of silicon nitride and bamboo powder as a wear-resistant filler. Silicon nitride is a ceramic material with excellent properties and very high hardness. When added to the coating, it forms a dense three-dimensional structure of organic polymer and inorganic filler, improving the coating's wear, scratch, and abrasion resistance, while also enhancing its durability. The addition of bamboo powder can partially replace silicon nitride, reducing costs while maintaining the coating's excellent mechanical properties. It also helps improve the coating's adhesion to the wall and its low-temperature performance. DETAILED DESCRIPTION
[0029] The present application is further described in detail below with reference to the examples. It is particularly noted that if no specific conditions are specified in the following examples, the reactions are carried out according to conventional conditions or the conditions recommended by the manufacturer. Unless otherwise specified, the raw materials used in the following examples can be obtained from common commercial sources.
[0030] The examples of this application use the following raw materials: Glass fiber, with an average diameter of 10 μm and a length of 3 mm; epoxy resin, brand E-44, was purchased from Henan Shuizhihuan Industrial Co., Ltd. Polycarboxylate ammonium salt dispersant, model AG-35, was purchased from Guangdong Zhongtai Lianhua New Materials Co., Ltd.
[0031] The silicone leveling agent, model EFKA 3035; the mineral oil defoaming agent, model MO 2157; and the preservative, model Protectol PE, are all manufactured by BASF.
[0032] Preparation Example 1: The preparation process of modified epoxy acrylic emulsion is as follows: In the first step, 3 kg of vinyl triethoxysilane and 20 kg of 70 wt% ethanol solution were mixed, heated to 35 ° C, and stirred for 20 minutes to obtain a modified solution; In the second step, 10 kg of glass fiber and 60 kg of water were mixed evenly, ultrasonically dispersed for 30 minutes, and then the above-mentioned modification liquid was added. The temperature was raised to 60 ° C and stirred for 2 hours. Then, it was filtered, washed with water, and dried to obtain modified glass fiber. In the third step, all the modified glass fibers were added to 80 kg of water, ultrasonically dispersed for 30 minutes, and then 0.3 kg of sodium dodecylbenzene sulfonate was added. The temperature was raised to 55 ° C., and then a mixture of 6 kg of epoxy resin, 20 kg of methyl methacrylate, 30 kg of butyl acrylate and 2 kg of methacrylic acid was added. The temperature was then raised to 70 ° C. 2 kg of 10 wt% ammonium persulfate solution was added, stirred evenly, and reacted for 1 hour to obtain a modified epoxy acrylic emulsion.
[0033] Preparation Example 2: The preparation process of modified epoxy acrylic emulsion is as follows: In the first step, 5 kg of vinyl triethoxysilane and 30 kg of 80 wt% ethanol solution were mixed, heated to 40°C, and stirred for 30 minutes to obtain a modified solution; In the second step, 15 kg of glass fiber and 80 kg of water were mixed evenly, ultrasonically dispersed for 60 minutes, and then the above-mentioned modification liquid was added. The temperature was raised to 70 ° C and stirred for 3 hours. Then, it was filtered, washed with water, and dried to obtain modified glass fiber. In the third step, all the modified glass fibers were added to 100 kg of water, ultrasonically dispersed for 60 minutes, and then 0.5 kg of sodium dodecylbenzene sulfonate was added. The temperature was raised to 60 ° C. Then, a mixture of 8 kg of epoxy resin, 25 kg of methyl methacrylate, 40 kg of butyl acrylate and 3 kg of methacrylic acid was added. The temperature was then raised to 75 ° C. 3 kg of 10 wt% ammonium persulfate solution was added, stirred evenly, and reacted for 2 hours to obtain a modified epoxy acrylic emulsion.
[0034] Preparation Example 3: The preparation process of modified epoxy acrylic emulsion is as follows: In the first step, 4 kg of vinyl triethoxysilane and 25 kg of 75 wt% ethanol solution were mixed, heated to 38 ° C, and stirred for 25 minutes to obtain a modified solution; In the second step, 12 kg of glass fiber and 70 kg of water were mixed evenly, ultrasonically dispersed for 45 minutes, and then the above-mentioned modification liquid was added. The temperature was raised to 65 ° C and stirred for 2.5 hours. Then, it was filtered, washed with water, and dried to obtain modified glass fiber. In the third step, all the modified glass fibers were added to 90 kg of water, ultrasonically dispersed for 45 minutes, and then 0.4 kg of sodium dodecylbenzene sulfonate was added. The temperature was raised to 58 ° C. Then, a mixture of 7 kg of epoxy resin, 22 kg of methyl methacrylate, 35 kg of butyl acrylate and 2.5 kg of methacrylic acid was added. The temperature was then raised to 72 ° C. 2.5 kg of 10 wt% ammonium persulfate solution was added, stirred evenly, and reacted for 1.5 hours to obtain a modified epoxy acrylic emulsion.
[0035] Preparation Example 4: The preparation process of epoxy acrylic emulsion is as follows: mix 7 kg of epoxy resin, 22 kg of methyl methacrylate, 35 kg of butyl acrylate and 2.5 kg of methacrylic acid, heat to 72 ° C, add 2.5 kg of 10 wt% ammonium persulfate solution, stir evenly, react for 1.5 hours, and obtain epoxy acrylic emulsion.
[0036] Preparation Example 5: The preparation process of the compatibilizer is as follows: first, peel, core and chop the avocado, then heat it with steam to 100°C for 3 minutes, then use a screw oil press to press the steamed avocado at 60°C and 10 MPa, and then filter it to obtain the compatibilizer.
[0037] Preparation Example 6: The preparation process of the compatibilizer is as follows: first, peel, core and chop the avocado, then heat it with steam to 110°C for 5 minutes, then use a screw oil press to press the steamed avocado at a temperature of 80°C and a pressure of 20 MPa, and then filter it to obtain the compatibilizer.
[0038] Preparation Example 7: The preparation process of the compatibilizer is as follows: first, peel, core and chop the avocado, then heat it with steam to 105°C for 4 minutes, then use a screw oil press to press the steamed avocado at a temperature of 70°C and a pressure of 15 MPa, and then filter it to obtain the compatibilizer.
[0039] Example 1: A high-hardness, scratch-resistant artistic coating comprising the following components: 30 kg of modified epoxy acrylic emulsion, prepared in Preparation Example 1; 8 kg of wear-resistant filler, comprising silicon nitride and bamboo powder in a mass ratio of 2:1, with the particle size of the silicon nitride being 1 μm and the particle size of the bamboo powder being 1 μm; Titanium dioxide 15kg; 0.4 kg of polycarboxylate ammonium salt dispersant; 0.2kg of silicone leveling agent; Mineral oil defoamer 0.1kg; Preservative 0.1kg; 25kg of water.
[0040] A method for preparing a high-hardness, scratch-resistant artistic coating comprises the following steps: uniformly mixing the modified epoxy acrylic emulsion, wear-resistant filler, titanium dioxide, dispersant, leveling agent, defoamer, preservative and water according to the formula addition amount to obtain the high-hardness, scratch-resistant artistic coating.
[0041] Example 2: A high-hardness, scratch-resistant artistic coating comprising the following components: 40 kg of modified epoxy acrylic emulsion, prepared in Preparation Example 2; 10 kg of wear-resistant filler, comprising silicon nitride and bamboo powder in a mass ratio of 3:1, with the particle size of the silicon nitride being 1 μm and the particle size of the bamboo powder being 1 μm; Titanium dioxide 20kg; Polycarboxylic acid ammonium salt dispersion 0.8 kg; 0.5kg of silicone leveling agent; Mineral oil defoamer 0.3kg; Preservative 0.2kg; 35kg of water.
[0042] A method for preparing a high-hardness, scratch-resistant artistic coating comprises the following steps: uniformly mixing the modified epoxy acrylic emulsion, wear-resistant filler, titanium dioxide, dispersant, leveling agent, defoamer, preservative and water according to the formula addition amount to obtain the high-hardness, scratch-resistant artistic coating.
[0043] Example 3: A high-hardness, scratch-resistant artistic coating comprising the following components: 35 kg of modified epoxy acrylic emulsion, prepared in Preparation Example 3; 9 kg of wear-resistant filler, comprising silicon nitride and bamboo powder in a mass ratio of 3:1, with the particle size of the silicon nitride being 1 μm and the particle size of the bamboo powder being 1 μm; Titanium dioxide 18kg; 0.6 kg of polycarboxylate ammonium salt dispersant; 0.3kg of silicone leveling agent; Mineral oil defoamer 0.2kg; Preservative 0.15kg; 30kg of water.
[0044] A method for preparing a high-hardness, scratch-resistant artistic coating comprises the following steps: uniformly mixing the modified epoxy acrylic emulsion, wear-resistant filler, titanium dioxide, dispersant, leveling agent, defoamer, preservative and water according to the formula addition amount to obtain the high-hardness, scratch-resistant artistic coating.
[0045] Example 4: The only difference from Example 3 is that 2 kg of the compatibilizer prepared in Preparation Example 5 is also included.
[0046] Example 5: The only difference from Example 3 is that 3 kg of the compatibilizer prepared in Preparation Example 6 is also included.
[0047] Example 6: The only difference from Example 3 is that 2.5 kg of the compatibilizer prepared in Preparation Example 7 is also included.
[0048] Example 7: The only difference from Example 6 is that the added amount of wear-resistant filler is 13 kg.
[0049] Example 8: The only difference from Example 6 is that the added amount of wear-resistant filler is 14 kg.
[0050] Example 9: The only difference from Example 6 is that the added amount of wear-resistant filler is 15 kg.
[0051] Example 10: The only difference from Example 3 is that the added amount of wear-resistant filler is 15 kg.
[0052] Example 11: The only difference from Example 6 is that the particle size of silicon nitride is 5 μm and the particle size of bamboo powder is 0.3 μm.
[0053] Example 12: The only difference from Example 6 is that the particle size of silicon nitride is 10 μm and the particle size of bamboo powder is 0.5 μm.
[0054] Example 13: The only difference from Example 6 is that the particle size of silicon nitride is 8 μm and the particle size of bamboo powder is 0.4 μm.
[0055] Example 14: The only difference from Example 6 is that the wear-resistant fillers are all silicon nitride.
[0056] Comparative Example 1: The only difference from Example 3 is that the modified epoxy acrylic emulsion is replaced by the epoxy acrylic emulsion prepared in Preparation Example 4.
[0057] Comparative Example 2: The only difference from Example 3 is that the wear-resistant filler is replaced by light calcium carbonate.
[0058] Performance testing: The hardness of the artistic coatings of Examples 1-14 and Comparative Examples 1 and 2 was tested with reference to the method described in GB / T 6739-2022 "Determination of film hardness by pencil method for paints and varnishes". The results obtained are pencil hardness, which are recorded in Table 1.
[0059] The scratch resistance of the artistic coatings of Examples 1-14 and Comparative Examples 1 and 2 was tested with reference to the method described in GB / T 9279.1-2015 "Determination of Scratch Resistance of Paints and Varnishes - Part 1: Constant Load Method". The tests were conducted at ambient temperatures of 23°C and 0°C, respectively, with an increment of 0.5 N each time. The results were the minimum load that caused scratching, and the results are recorded in Table 1.
[0060] Table 1 Coating performance test result record From Table 1, we can get: 1. The coating of this application has high hardness and scratch resistance, meeting the durable use requirements of high-end decoration; 2. Combining the test data of Comparative Example 1 and Example 3, it can be seen that after the epoxy acrylic emulsion is modified, the hardness is slightly improved and the scratch resistance is significantly improved, especially in low temperature environments; 3. Comparison of the test data of Examples 1-10 shows that the compatibilizer can improve the compatibility of the wear-resistant filler and the film-forming resin, so that the addition amount of the wear-resistant filler can be increased, thereby improving the scratch resistance of the coating; 4. By comparing the test data of Example 6 with those of Examples 11-13, it can be seen that the particle sizes of silicon nitride and bamboo powder are optimized to optimize the scratch resistance of the coating. 5. Comparison of the test data of Example 6 and Example 14 shows that the addition of bamboo powder promotes the low-temperature scratch resistance of the coating.
[0061] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed, but as long as they are within the scope of the claims of the present application, they are protected by the patent law.
Claims
1. A high-hardness, scratch-resistant artistic coating, characterized in that: The composition comprises the following components in parts by weight: 30-40 parts of modified epoxy acrylic emulsion; 8-15 parts of wear-resistant filler; 15-20 parts of titanium dioxide; Dispersant 0.4-0.8 parts; Leveling agent 0.2-0.5 parts; Defoaming agent 0.1-0.3 parts; Preservative 0.1-0.2 parts; 25-35 parts water; The preparation process of the modified epoxy acrylic emulsion is as follows: The first step is to mix 3-5 parts of vinyl triethoxysilane and 20-30 parts of 70-80wt% ethanol solution by weight, heat to 35-40°C, and stir for 20-30 minutes to obtain a modified solution; The second step is to mix 10-15 parts of glass fiber and 60-80 parts of water, add the above-mentioned modified liquid after ultrasonic dispersion for 30-60 minutes, heat to 60-70°C, continue stirring for 2-3 hours, then filter, wash with water, and dry to obtain modified glass fiber; The third step is to add all the modified glass fibers into 80-100 parts of water, ultrasonically disperse for 30-60 minutes, then add 0.3-0.5 parts of sodium dodecylbenzene sulfonate, heat to 55-60°C, then add a mixture of 6-8 parts of epoxy resin, 20-25 parts of methyl methacrylate, 30-40 parts of butyl acrylate and 2-3 parts of methacrylic acid, then heat to 70-75°C, add 2-3 parts of 10wt% ammonium persulfate solution, stir evenly, react for 1-2 hours, and obtain a modified epoxy acrylic emulsion.
2. The high-hardness, scratch-resistant artistic coating according to claim 1, characterized in that: The wear-resistant filler includes silicon nitride and bamboo powder in a mass ratio of (2-3):
1.
3. The high-hardness, scratch-resistant artistic coating according to claim 2, characterized in that: By weight, it also includes 2-3 parts of a compatibilizer; The preparation process of the bulking agent is as follows: first peel, core and chop avocados, then heat them with steam to 100-110° C. for 3-5 minutes, then use a screw oil press to press the steamed avocados, the pressing temperature is controlled at 60-80° C., the pressure is 10-20 MPa, and the bulking agent is obtained after filtering.
4. The high-hardness scratch-resistant artistic coating according to claim 3, characterized in that: The added amount of the wear-resistant filler is 13-15 parts.
5. The high-hardness, scratch-resistant artistic coating according to claim 2, characterized in that: The particle size of the silicon nitride is 5-10 μm, and the particle size of the bamboo powder is 0.3-0.5 μm.
6. The high-hardness, scratch-resistant artistic coating according to claim 1, characterized in that: The dispersant is a polycarboxylate ammonium salt dispersant.
7. The high-hardness, scratch-resistant artistic coating according to claim 1, characterized in that: The leveling agent is an organic silicon leveling agent.
8. The high-hardness, scratch-resistant artistic coating according to claim 1, characterized in that: The defoamer is a mineral oil defoamer.
9. A method for preparing a high-hardness, scratch-resistant artistic coating according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: mixing modified epoxy acrylic emulsion, wear-resistant filler, titanium dioxide, dispersant, leveling agent, defoamer, preservative and water according to the required weight proportion of the formula to obtain high-hardness scratch-resistant artistic coating.
10. Use of the high-hardness, scratch-resistant artistic paint according to any one of claims 1 to 8 in wall decoration.
Citation Information
Patent Citations
TiO2 nanowire modified epoxy acrylic resin anticorrosive coating and preparation method thereof
CN111393944A
High-hardness scratch-resistant artistic coating as well as preparation method and application thereof
CN114231099A
